Dentistry for Nigerians with special needs: an overview - H. B. Waldman; F. A. Oredugba; S. P. Oredugba (Nigerian Dental Association, 2010)
There are approximately 25 million residents with disabilities in Nigeria. Social inclusion of individuals with disabilities is difficult since societal views of these persons are in terms of charity and welfare rather than functioning members of a community. While there are no national studies of the dental needs of individuals with disabilities in Nigeria, there are reports of local studies of patients with disabilities which indicate a greater incidence of management difficulties as well as the need for improved oral hygiene and restorative services. Nevertheless, a study of practitioner involvement in the care of individuals with disabilities reported limited preparation of dental students to provide service for this population. Some organizations, such as the Special Olympics Healthy Athletes Special Smiles and the Smile Train, have set up programmes, both educational and service, to address some of their oral health issues. It is recommended that there is a need to identify the availability of current dental service centers for individuals with disabilities, establish a national organization to stimulate an awareness of the varied needs of individuals with disabilities and real programs in schools to prepare dental students to care for individuals with disabilities. Examples of dental education accreditation standards in other countries are used as models for the improvement in the preparation of dental students to provide services for individuals with special needs.